2015
DOI: 10.1021/acs.macromol.5b00337
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Crystallization and Ionic Liquid Induced Partial β-Phase Transformation of Poly(vinylidene fluoride) Nanoparticles

Abstract: Colloidal crystallization of poly­(vinylidene fluoride) (PVDF) nanoparticles (NPs) and its β-phase transformation were studied. The pristine PVDF NPs with an average diameter of 230 nm consist of 46% α-phase and 54% amorphous PVDF. The PVDF NPs were assembled on a quartz substrate by means of vertical deposition method from a tetrahydrofuran dispersion of PVDF NPs with a few volume percentage of n-alkane. The resultant colloidal thin films displayed a pale-greenish structural color with the selective reflectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…Figure The presence of IL also contributes for the formation of the β-phase, as also reported in the literature [36]. For example, the diffraction peak at 2 = 20.6° can be detected even for blend containing 10 wt% of PAni.DBSA and prepared in the presence of IL.…”
Section: Structural and Morphological Characterizationssupporting
confidence: 77%
See 1 more Smart Citation
“…Figure The presence of IL also contributes for the formation of the β-phase, as also reported in the literature [36]. For example, the diffraction peak at 2 = 20.6° can be detected even for blend containing 10 wt% of PAni.DBSA and prepared in the presence of IL.…”
Section: Structural and Morphological Characterizationssupporting
confidence: 77%
“…In this context, the modification of PVDF and PVDF -based copolymer matrices with imidazolium -based ionic liquids has been reported mainly with the aim of developing new polymeric gel electrolyte membranes for proton exchange fuel cell [32] and for energy storage applications [33][34][35]. Okada et al [36] have also reported the ability of ionic liquid in inducing the β-phase formation of PVDF. ILs have also been successfully employed to improve the dispersion of carbon nanotubes within the PVDF matrix [37].…”
Section: Introductionmentioning
confidence: 99%
“…The latest case is that PVDF nanoparticles with α-phase were partly transformed into β-one by adding imidazolium nitrate IL and subsequent thermal annealing below the melting temperature. 27 Although the influence of IL on the structure of PVDF (mainly focusing on the formation of polar crystalline phase) has been observed above, the mechanism for the structuration is quite elusive. From current understanding, dipolar interactions between PVDF chain molecules and ILs contribute the formation of polar crystalline phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigations on poly(vinylidene fluoride) (PVDF) modified by room temperature ionic liquids (ILs) have been widely reported in the literatures . The incorporation of ILs leads to the formation of electroactive phases ( β or γ phase) of PVDF . PVDF/IL blends have the potential applications as solid polymer electrolytes, actuators, biomedical devices, and smart materials .…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45] The incorporation of ILs leads to the formation of electroactive phases ( β or γ phase) of PVDF. [36][37][38][39][40][41][42] PVDF/IL blends have the potential applications as solid polymer electrolytes, [ 43 ] actuators, [ 44 ] biomedical devices, [ 45 ] and smart materials. [ 46 ] It has been demonstrated that PVDF is thermodynamically miscible with IL due to the specifi c interaction [ 37,38 ] between >CF 2 with cations of IL.…”
Section: Introductionmentioning
confidence: 99%